The cleanliness differences of root canal walls after irrigated with East Java propolis extract and sodium hypoclorite solutions - Tamara Yuanita (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Root canal instrumentation produces smear layer that covers dentine tubules of the root canal surface. Smear layer is organic and inorganic particles that have to be removed. East Java propolis extracts contais of saponin components used as a natural surfactant. 2.5% NaOCl and 5% NaOCl solutions have been widely used for irrigation in root canal treatment. Purpose: The purpose of this study was to analyze the cleanliness of the root canal walls, irrigated with aquadest, 8% East Java propolis extract, 2.5% NaOCl and 5% NaOCl. Method: Forty extracted teeth with straight single root canals were randomly divided into four groups(n=10). The specimens were prepared with ProTaper. During instrumentation, the root canals were irrigated with different solutions: Control Group irrigated with aquadest; Group 1 irrigated with 8% East Java propolis extract; Group 2 irrigated with 2.5% NaOCl and Group 3 irrigated with 5% NaOCl. The root canals were cut at apical third and SEM scores were tested by using Mann-Whitney test at the significance level of p=0.05 and Median Control test. Result: The results of Mann-Whitney Test, there were significant differences between control group with Group 1, 2 and 3 (p<0.05). Based on the Median Control test, the value of 8% East Java propolis extracts was 1,000, which was the best value compared to 2.5% NaOCl, 5% NaOCl and aquadest. Conclusion: It can be concluded that 8% East Java propolis extract is the most effective solution for cleaning root canal walls compared with 2.5% NaOCl and 5% NaOCl.